A Game Changer: A Multifunctional Perovskite Exhibiting Giant Ferroelectricity and Narrow Bandgap with Potential Application in a Truly Monolithic Multienergy Harvester or Sensor - Bai, Yang; Tofel, Pavel; Palosaari, Jaakko; Jantunen, Heli; Juuti, Jari (Advanced materials (Deerfield Beach, Fla.), 2017)
An ABO3 -type perovskite solid-solution, (K0.5 Na0.5 )NbO3 (KNN) doped with 2 mol% Ba(Ni0.5 Nb0.5 )O3-δ (BNNO) is reported. Such a composition yields a much narrower bandgap (≈1.6 eV) compared to the parental composition-pure KNN-and other widely used piezoelectric and pyroelectric materials (e.g., Pb(Zr,Ti)O3 , BaTiO3 ). Meanwhile, it exhibits the same large piezoelectric coefficient as that of KNN (≈100 pC N-1 ) and a much larger pyroelectric coefficient (≈130 µC m-2 K-1 ) compared to the previously reported narrow-bandgap material (KNbO3 )1-x -BNNOx . The unique combination of these excellent ferroelectric and optical properties opens the door to the development of multisource energy harvesting or multifunctional sensing devices for the simultaneous and efficient conversion of solar, thermal, and kinetic energies into electricity in a single material. Individual and comprehensive characterizations of the optical, ferroelectric, piezoelectric, pyroelectric, and photovoltaic properties are investigated with single and coexisting energy sources. No degrading interaction between ferroelectric and photovoltaic behaviors is observed. This composition may fundamentally change the working principles of state-of-the-art hybrid energy harvesters and sensors, and thus significantly increases the unit-volume energy conversion efficiency and reliability of energy harvesters in ambient environments.
Keywords: multisource energy harvesting; piezoelectrics; photovoltaics; pyroelectrics